Evaluation of Myo-Inositol as a Potential Biomarker for Depression in Schizophrenia - Chiappelli, Joshua (Neuropsychopharmacology, 2015)
Depression is highly prevalent in patients with schizophrenia and is associated with significant clinical consequences, but there is no known biomarker for depression in schizophrenia. One of the putative neurochemical biomarkers for depression in major depressive disorder (MDD) is reduced cerebral concentration of myo-Inositol. We examined whether myo-Inositol levels provide a potential marker for depressive symptoms in schizophrenia similar to that in MDD and are informative regarding causal biological pathways underlying both depression and schizophrenia. We used proton magnetic resonance spectroscopy to examine myo-Inositol levels in the anterior cingulate cortex (ACC) in 59 schizophrenia spectrum disorder (SSD) patients and 69 matched community comparison participants. Participants completed the Maryland Trait and State Depression (MTSD) scale to measure symptoms of depression experienced around time of assessment (‘State’ subscale) and longitudinally (‘Trait’ subscale). Myo-Inositol in the ACC was negatively correlated with MTSD-Trait scores in both patients (ρ=−0.336, p=0.009) and community comparison samples (ρ=−0.328, p=0.006). Furthermore, patients with a diagnosis of schizoaffective disorder or a history of at least one major depressive episode had lower levels of myo-Inositol compared with schizophrenia patients without a current or past affective diagnosis (p=0.012). Since reduced brain myo-Inositol is associated with MDD, myo-Inositol may be a biochemical marker of depressive mood symptoms across diagnostic boundaries. If confirmed, this finding may aid investigation of the pathophysiology and therapeutics of depression common between depression, schizophrenia and other psychiatric diagnoses.